2005
DOI: 10.1111/j.1525-1438.2005.15353.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of gemcitabine-based combinations for platinum-resistant ovarian cancer

Abstract: Gemcitabine, an analog of deoxycytidine, is an anticancer nucleoside with proven activity in different solid malignancies. The efficacy of gemcitabine as a single agent or as part of a combination treatment has been evaluated in several trials, and antitumor activity has been observed in patients with sensitivity and resistance to both platinum and paclitaxel. In this context, preclinical studies have shown that gemcitabine-based combinations increase the cytotoxic action of the treatment and can potentially o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although chemotherapy regimens for primary and platinum-sensitive recurrent ovarian cancers have been determined based on phase III studies, recommended regimens for platinumand/or paclitaxel-refractory recurrent ovarian cancer have yet to be determined. Sehouli 25 reviewed the effects of gemcitabine-based combination therapy for platinum-resistant ovarian cancer, and reported that although gemcitabine in combination with paclitaxel, pegylated liposomal doxorubicin, or topotecan appeared to yield higher response rates than those historically observed with monotherapy, it is still unknown whether combination therapy is superior to monotherapy, especially as salvage therapy for heavily pretreated patients. We have demonstrated that the status of tumor microsatellite regions was changed from stable to unstable by platinum-based chemotherapy, 26 and in our more recent study, we have clarifi ed that hMLH1 promoter methylation is also changed by platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Although chemotherapy regimens for primary and platinum-sensitive recurrent ovarian cancers have been determined based on phase III studies, recommended regimens for platinumand/or paclitaxel-refractory recurrent ovarian cancer have yet to be determined. Sehouli 25 reviewed the effects of gemcitabine-based combination therapy for platinum-resistant ovarian cancer, and reported that although gemcitabine in combination with paclitaxel, pegylated liposomal doxorubicin, or topotecan appeared to yield higher response rates than those historically observed with monotherapy, it is still unknown whether combination therapy is superior to monotherapy, especially as salvage therapy for heavily pretreated patients. We have demonstrated that the status of tumor microsatellite regions was changed from stable to unstable by platinum-based chemotherapy, 26 and in our more recent study, we have clarifi ed that hMLH1 promoter methylation is also changed by platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…These characteristics make gemcitabine an attractive partner for combinations with other cytostatic agents. 22 Several studies have confirmed its efficacy in treating platinum-resistant or platinum-sensitive recurrent ovarian cancer. 23 26 In Yoshino study, the CBR of gemcitabine monotherapy for recurrent or persistent CCC was as high as 60% (3/5).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue (grade2) is frequently the worst toxicity, nausea (grade3) and neutropenia (grade3 and 4) are also statistically frequent in gemcitabine, and PPE is more frequent in PLD [14] (Table 4). The different mechanisms and noncross-resistance of gemcitabine can be expected to overcome drug resistance in combination with other nonplatinum drugs [34]. A combination of gemcitabine (1000 mg/m 2 ) with weekly paclitaxel (80 mg/m 2 ) on days 1, 8 and 15 q/4w showed a 40% response rate and the median PFS was 5.7 months for 35 patients with platinum resistant disease [12].…”
Section: Treatment Option For Recurrencementioning
confidence: 99%